Management Strategy and Challenges for Religious Radio Stations in Malaysia - Juliana Abdul Wahab; Intan Soliha Ibrahim; Azlan Abas (Kulliyyah of Islamic Revealed Knowledge and Human Sciences International Islamic University Malaysia, 2023)
The landscape of radio transmission has changed as a result of the advent of digital technologies. It has indirectly affected how people listen to the radio. This study seeks to understand how religious radio stations stay relevant in radio industry when commercial radio rules. Hence, this research aims to determine the factors contributing to religious radio sustainability and its challenges in the digital age. This research used a qualitative approach by interviewing religious radio station managers. The findings reveal that management strategy is the core factor influencing community response to religious radio. Even though commercial radio dominates the radio business in the country, there is no competition between religious and commercial radio. Nevertheless, the commercial radio seeks to emulate religious radio strategy, unexpectedly. By defining the target listeners and using a good scheduling structure, management has proven to be the cornerstone of religious radio stations' success.